2019
DOI: 10.1093/mnras/stz1855
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the optical light curves of hydrogen-rich and hydrogen-poor type II supernovae

Abstract: ABSTRACT Type II supernovae (SNe II) show strong hydrogen features in their spectra throughout their whole evolution, while type IIb supernovae (SNe IIb) spectra evolve from dominant hydrogen lines at early times to increasingly strong helium features later on. However, it is currently unclear whether the progenitors of these SN types form a continuum in pre-SN hydrogen mass or whether they are physically distinct. SN light-curve morphology directly relates to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 112 publications
1
30
0
2
Order By: Relevance
“…Filippenko et al 1993). A recent study analysed the possible existence of a continuum between the SNe II and IIb in terms of their photometric properties (Pessi et al 2019). However, these latter authors found clear differences between the two subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Filippenko et al 1993). A recent study analysed the possible existence of a continuum between the SNe II and IIb in terms of their photometric properties (Pessi et al 2019). However, these latter authors found clear differences between the two subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Faran et al (2014), analysing a sample of fast-declining SNe II, found that SNe IIL seem to be photometrically related to SNe IIb. More recently, Pessi et al (2019), using a larger sample of SNe (73 SNe II and 22 SNe IIb), found a lack of events that bridge the observed properties of these two classes, concluding that they form two observationally distinct families.…”
mentioning
confidence: 99%
“…DES14X2fna rises to peak in the r band in 18 d, similar to ASASSN-18am and SN 2011hs and fairly typical for SNe IIb based on the sample of SN IIb rise times presented in fig. 4 of Pessi et al (2019). After rising to maximum, DES14X2fna declines at a similar rate to ASASSN-18am until ∼30 d after explosion, after which DES14X2fna begins to decline far more rapidly.…”
Section: Photometrymentioning
confidence: 71%